PROTOTIPE SISTEM PENDETEKSI HUJAN BERBASIS ARDUINO UNO MENGGUNAKAN SENSOR RAIN YL-83 - Akhlis Munazilin; Islamiyatul Addewiyah; Fitra Lia Shofiah (CV. Denasya Smart Publisher, 2026)
Rain detection systems are essential in tropical countries such as Indonesia, where sudden rainfall can occur and cause significant losses including wet laundry, localized flooding, and disruptions to outdoor activities. This research aims to design and implement an Arduino UNO-based rain detection prototype utilizing the YL-83 Rain Sensor module. The system employs an ATmega328P microcontroller to process analog signals from the rain sensor through its 10-bit Analog-to-Digital Converter (ADC). When the sensor's ADC reading is less than or equal to 400, indicating the presence of rainwater on the sensor surface, the system activates a buzzer alarm and illuminates a red LED indicator. Conversely, when the ADC value exceeds 400, indicating dry conditions, the buzzer is deactivated and a green LED is illuminated. The circuit was assembled on a breadboard following a Fritzing schematic, with the sensor's AO pin connected to Arduino's A0 analog input, buzzer to digital pin 7, red LED to pin 9, and green LED to pin 8, each LED using a 220-ohm current-limiting resistor. Testing across 15 data points demonstrated 100% detection accuracy in distinguishing rain from non-rain conditions, with ADC values ranging from 230–400 for rain conditions and 501–1023 for dry conditions. The system demonstrates reliable, low-cost performance as a rain detection alert mechanism and offers a strong foundation for future IoT-enabled enhancements such as wireless notification via ESP8266/ESP32 integration..